EFEITO DA TEMPERATURA SOBRE O CRESCIMENTO DE JUVENIS DE CARAPEVA Eugerres brasilianus: Effect of temperature on juvenile growth of Brazilian mojarra, Eugerres brasilianus - Passini, Gabriel; Vaz Avelar de Carvalho, Cristina; Kaway, Martim; Shizuo Owatari, Marco; Ronzani Cerqueira, Vinicius (Arquivos de Ciências do Mar, 2024)
The Brazilian mojarra Eugerres brasilianus is an omnivorous fish that is widely distributed along the Brazilian coast and has potential for estuarine fish farming. The objective of this study was to evaluate the growth performance of mojarra juveniles at different temperatures. The juveniles used had initial weight and total length of 0.73 ± 0.14 g and 3.96 ± 0.21 cm, respectively. Three temperatures (22, 26 and 30˚C) were tested with 4 repetitions each, for 45 days. The experimental units were 100 L tanks, with 50 fish per repetition and the temperature was maintained by submersible heaters with thermostat. Feeding was 8 times a day with commercial feed (45% crude protein). At the end of the experiment, survival was 84.00%, 97.50% and 90.50% in treatments 22, 26 and 30°C, respectively, being lower (P < 0.05) in treatment 22°C. Treatments showed significant differences (P < 0.05) for weight gain, total length and final weight, specific growth rate, feed intake and condition factor, with the best results in the 30°C treatment. Feed conversion did not differ significantly at tested temperatures. Based on the results, it is concluded that the Brazilian mojarra has a greater potential for rearing at 30˚C. Keywords: Nursery, marine fish culture, caratinga.